1973
DOI: 10.1093/jaoac/56.6.1369
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chicks and Rats as Test Animals for Studying Bioavailability of Iron, with Special Reference to Use of Reduced Iron in Enriched Bread

Abstract: Study was continued on the animal hemoglobin repletion test for measuring bioavailability of iron. With most iron sources, similar results were obtained with chicks and with rats. An important exception was noted with reduced iron. Seventeen samples were tested for solubility in dilute HCl and for bioavailability when fed to chicks and rats. The chicks utilized all samples reasonably well, but the rats were not able to efficiently utilize samples with particle sizes greater than 325 mesh. The mean relative bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
2

Year Published

1976
1976
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
4
2
Order By: Relevance
“…The RBV of electrolytic iron obtained by us was less than the 45-50% reported by Pla et al (1973) and Pennell et al (1975). Similarly Pla et al (1973) found the RBV of carbon monoxide reduced iron powder to be 19% whereas our corresponding result is only 12%.…”
Section: Resultscontrasting
confidence: 76%
See 1 more Smart Citation
“…The RBV of electrolytic iron obtained by us was less than the 45-50% reported by Pla et al (1973) and Pennell et al (1975). Similarly Pla et al (1973) found the RBV of carbon monoxide reduced iron powder to be 19% whereas our corresponding result is only 12%.…”
Section: Resultscontrasting
confidence: 76%
“…Shah and Belonje (1973a) employed a photographic-microscopic method for the determination of particle size distribution whereas Motzok et al (1975) used air elutriation to separate designated fractions. Pla et al (1973) separated particles larger than 32 µ by sieving. Since these methods are based on varying physical principles the results are not comparable.…”
mentioning
confidence: 99%
“…Different preparations of FePO, exhibit different solubilities and hence different levels of bioavailability (Harrison et al 1976). The solubility of the FePO, (Albright & Wilson, Warley, West Midlands) used to fortify the malted cocoa drink was measured by mechanically shaking 20 mg of the Fe salt with 100 ml 0.1 Mhydrochloric acid and quantitatively collecting any residue on filter paper as described by Pla et al (1973). Amounts ( 1 g) of the three samples of powdered drink were also tested for Fe solubility at 37' but in this case the filtrate was analysed for Fe by atomic absorption spectrophotometry (AAS) in order to measure solubility.…”
Section: Solubility Of Fepomentioning
confidence: 99%
“…The procedure of Pla et al (1973) was used to determine the relative solubilities of the iron fortification sources. A 20 mg sample of each iron source was mechanically shaken for 3 hr at room temperature with 100 ml of 0.1N HCI, and the residue collected and weighed on tared filter paper.…”
Section: Physical-chemical Characterizationmentioning
confidence: 99%
“…The lack of a consistent baking effect on relative availability seen in this study has also been observed by other workers. Verma et al (1977) and Pla et al (1973) found that reduced iron had similar RBV to rats whether it was added directly to the diet or baked into bread and then added to the diet. C o c c o d f i et al (1976) reported that processing iron fortification sources into a bran flake breakfast cereal did not significantly alter the KBV of the sources to rats.…”
Section: -Continued On Next Pagementioning
confidence: 99%